Fertile Tetraploids: New Resources for Future Rice Breeding? - Koide, Yohei; Kuniyoshi, Daichi; Kishima, Yuji (Frontiers in Plant Science, 2020)
Ploidy manipulation is an efficient technique for the development of novel phenotypes in plant breeding. However, in rice (Oryza sativa L.), severe seed sterility has been considered a barrier preventing cultivation of autotetraploids since the 1930s. Recently, a series of studies identified two fertile autotetraploids, identified herein as the PMeS (Polyploid Meiosis Stability) and Neo-Tetraploid lines. Here, we summarize their characteristics, focusing on the recovery of seed fertility, and discuss potential future directions of study in this area, providing a comprehensive understanding of current progress in the study of fertile tetraploid rice, a classical, but promising, concept for rice breeding.